Internet of Things Software Modules Marketplace - João Pedro Furriel de Moura Pinheiro (2020)
The advent of the Cyber-Physical Systems (CPS), a physical system representation through a vir-tual model, usually used to control a system or a process comes from the growing democratizationof the computational power. Nowadays, virtually anything can be equipped with some kind ofembedded processor to automate tasks, generate or consume some kind of data. In addition, thecontinuous development and improvement of the communication networks has helped leveragethe concept of the Internet of Things (IoT) in which things are now, themselves, connected to theInternet, exchanging data with each other and with people.In the industrial sector, CPS, also called Cyber-Physical Production Systems (CPPS) and theIoT are the main technological advances that lead to the industry fourth revolution, common des-ignated as Industry 4.0 in which the factory floor is no longer a centralized model where all thecomputation is done centrally but is now a decentralized model where industrial equipment haveembedded devices to control, automate tasks and react in a dynamic and intelligent manner to thesensed physical environment.Thereby, one of the keywords around the CPPSs is software. Software is no longer centralizedand is now distributed through several devices that comprises the system. This new approachcomes with significant changes and one of them is the reuse and distribution of the software. Itis not viable to manual deploy and install software in hundreds or thousands of devices and nothaving a way of reusing the existing software. If, on the one hand, the desire is to develop a moreintelligent process control system, on the other, flexibility, adaptability and simplicity are alsoconvenient capabilities or else intelligent manufacturing process control systems are built upon alot of resources debt. Hence, the solution is to build standards, tools and frameworks that allowthe reuse of software and its rapid deployment in the distributed devices.One option, in the Industry 4.0 field, to cope with the software reuse issue in this kind of sys-tems is the encapsulation of software in functional blocks, the Function Blocks (FBs) and their usein the function block programming paradigm, described in IEC 61499 standard. The functionalityis abstracted away in the FBs and can be reused by just deploying the them to the devices. Thisway, it is easier to manage a network by dragging and dropping these blocks, building complexapplications centrally and deploy everything to the distributed embedded devices. However, theimplementation of this standard to address the aforementioned problem brings, itself, other neces-sities such as managing the FBs, monitoring them and their previous download by the embeddeddevices.This dissertation main goal is the development of a marketplace to manage and monitor of FBs in a IEC 61499 network envisioning the filling of the previous mentioned gaps in this kindof networks. The marketplace, integrated in a IEC 61499 global solution will not only enable thedistribution of FBs among the embedded devices in a IEC 61499 compliant CPPS but also manageFBs versions, functioning as a central repository of software components, having also monitoringand statistical features, allowing the detection of flaws or malfunctions and collect statistical datai iiabout FBs usage.